Acquisition, Persistence, and Clearance of Human Papillomavirus Infection Among Male Virgins Residing in Brazil, Mexico, and the United States. (18th November 2017) - Liu, Zhiyue; Nyitray, Alan G; Hwang, Lu-Yu; Swartz, Michael D; Abrahamsen, Martha; Lazcano-Ponce, Eduardo; Villa, Luisa L; Giuliano, Anna R
Abstract : This study followed up on male virgins from 3 countries for up to 6 years and observed incident human papillomavirus (HPV) infection in the genital area before sexual debut. After penetrative sex initiation, 45.5% of men acquired HPV within 24 months. Abstract: Background: Little is known about the natural history of human papillomavirus (HPV) infection in male virgins. This study estimated the incidence and clearance of genital HPV infection and the factors associated with these measures among men who denied at baseline ever having penetrative sex. Methods: A cohort of 4123 men residing in Brazil, Mexico, and the United States were followed every 6 months for up to 10 visits. Genital exfoliated cells were collected and genotyped for 36 HPV types. Eighty-seven men were classified as virgins and included for analysis. Cox proportional hazards models identified factors associated with the incidence and clearance of genital HPV infection. Results: The incidence rates for any HPV infection among virgins who did and those who did not initiate sex during follow-up were 26.2 and 14.6 cases/1000 person-months, respectively. After penetrative sex initiation, 45.5% of men acquired HPV within 24 months. Younger age, current smoking, no recent female sex partners, and prevalent HPV infection were associated with high-risk HPV clearance. Conclusion: Virgins who did not initiate sex during follow-up still acquired HPV infection, possibly through nonpenetrative sexual contact. Further prospective cohort studies are needed to better understand factors associated with HPV acquisition and clearance in male virgins and recent nonvirgins.